(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Today we can not imagine life without television, radio and the Internet, as they are the main sources of information. Man as a social individual feels the need to satisfy the information needs. It can not exist in an information vacuum. «The man who owns the information, controls the world», and so people are always trying to be aware of all the events that are closely linked to them. Media is the achievement of this goal. Because of this, we can specify a number of functions Media: by transmitting information provides stability in society, calls for tolerance, promotes the adoption of a «correct» decision, focuses public attention on anything in particular, or redirect their attention in a another direction, building and managing public opinion. There is no doubt that the media plays an important role in the formation of public opinion. Will the media to generate environmental awareness in our case? In this regard, we will consider and discuss the problem of the relationship between man and nature, try to organize all of the concepts of modern media and analyze the operations and technologies of the media to influence the human mind. Key words: media, media culture, globalization, a television journalism, internet, television, radio, publishing, movies, documentaries.